ADVOKASI MASYARAKAT DALAM PENYELESAIAN SENGKETA LINGKUNGAN HIDUP DI JATEN, KABUPATEN KARANGANYAR - Absori Absori (WARTA LPM, 2007)
The problem of this public service is how to realize the autonomicpeople power to do the advocate of environment in order to overcomethe environmental conflict. In the training of the advocate of environment,the victims of pollution—most of them are farmers and low educatedpeople— are very enthusiastic to join the training. They are curious toknow how to struggle for their polluted environment as the result of themisconduct of irresponsible companies. In the effort of this advocate ofenvironment, the NGO “Gita Pertiwi” also gives significant contribution.It tends to cooperate with the society in order to do the advocatingprocess. Yet, the previous activity is conducting dialogues with the societyabout the pollution problem. Besides, they attempt to facilitate the societyto figure and find out the solution of the problem.